Efektivitas Hubungan Kerjasama Indonesia-Australia Melalui Program Ausaid di Sektor Pendidikan Era Jokowi pada Tahun 2014-2019 - Jofanka Alfiano; Putri Hergianasari; Triesanto Romulo Simanjuntak; Muhammad Fahmi (Jurnal Indonesia Sosial Teknologi, 2022)
This paper will discuss how the cooperative relationship between Indonesia and Australia through AusAID resulted in various assistance programs in the education sector during the Joko Widodo era from 2014 to 2019, in which this research will look at the effectiveness of the cooperation. Indonesia has pressing problems in the education sector. This is due to the declining quality of education in Indonesia and the alarming dropout rate. Therefore, it is necessary to take steps to improve the quality of education in Indonesia, one of which is through cooperation with Australia. Bilateral relations between Indonesia and Australia have existed for a long time so cooperation in the education sector between the two countries is considered to be beneficial. Indonesia has various policies in the education sector such as 9-year compulsory education and character education development. Meanwhile, Australia has a foreign policy in the field of education that focuses on assistance in improving the quality of education and direct assistance. The cooperation between Indonesia and Australia in the field of education can be seen in the implementation of programs such as the Education Partnership, Technical Assistance for Education System Strengthening, ProDEP, and Innovation for Indonesia's School Children. The cooperation program resulted in various achievements, such as the availability of educational infrastructure and facilities, improving the quality of educators and educational services, improving the curriculum for effective learning methods, as well as the accessibility of education quality in achieving gender equality and being disability-friendly. The author uses Liberalism theory to describe how effective the cooperation between Indonesia and Australia in the Indonesian education sector is through AusAID. Researchers see that educational cooperation between Indonesia and Australia from 2014 to 2019 was effective in helping to overcome various educational issues in Indonesia.